Ответы и объяснения

Лучший Ответ!
2013-12-15T20:31:50+04:00
                             Решение:

=((asqrt(a)+bsqrt(b))/(a-b)-sqrt(a)+sqrt(b))*(a-b)/sqrt(ab)=(asqrt(a)+bsqrt(b)-asqrt(a)-bsqrt(b)+sqrt(b)a+sqrt(a)b)/(a-b)*(a-b)/sqrt(ab)=
=sqrt(ab)(sqrt(b)+sqrt(a))/sqrt(ab)=sqrt(a)+sqrt(b).

  • Участник Знаний
2013-12-16T00:13:47+04:00
1)(√a+√b)(a-√a√a+b)/(√a-√b)(√a+√b) - (√a-√b)(√a+√b)/(√a+√b)=(a-√a√b+b)/(√a-√b) - (√a-√b)=(a-√a√b+b-a+2√a√b-b)/(√a-√b)=√a√b/(√a-√b)
2)√a√b/(√a-√b) *(√a-√b)(√a+√b)/√a√b=√a+√b=1/3+1/6=3/6=1/2